Prediction of Srebp-1 as a Key Target of Qing Gan San Against MAFLD in Rats via RNA-Sequencing Profile Analysis - Yang, Bendong; Sun, Jingyue; Liang, Shufei; Wu, Peixuan; Lv, Rui; He, Yanping; Li, Deqi; Sun, Wenlong; Song, Xinhua (Frontiers in Pharmacology, 2021)
Metabolism-associated fatty liver disease (MAFLD) is the most common chronic liver disease worldwide, and the use of traditional Chinese medicines for the treatment of this disease has attracted increasing attention. The Qing Gang Sang formula (QGS), a well-known TCM, consists of Polygonatum sibiricum, the peel of Citrus reticulata Blanco, the leaves of Morus alba L, Cichorium intybus, Glycyrrhiza uralensis Fisch, and Cirsium setosum. Here, the objective of the present study was to uncover the anti-hyperlipidaemic and lowering hepatic fat accumulation effects and mechanisms of QGS in high-fat diet-induced MAFLD rats. Our results suggest that QGS significantly reduces the levels of total cholesterol (TC) and triglycerides (TG) in both serum and liver tissue and partially protects hepatic function. Moreover, we observed that QGS significantly ameliorates hepatic lipid accumulation via haematoxylin and eosin (H&E) staining. Furthermore, RNA sequencing was used to further investigate the key genes involved in the development and treatment of MAFLD. The results indicated that QGS had 222 potential therapeutic targets associated with MAFLD. Hierarchical clustering analysis showed that the gene expression trend in rats with MAFLD was reversed to normal after QGS treatment. Enrichment analysis revealed that QGS affects biological functions/pathways such as the regulation of lipid metabolic processes (GO:0019216) and the non-alcoholic fatty liver disease pathway (hsa04932) and identified Srebp-1 as a key regulator in the synthesis of cholesterol and TGs. Subsequently, both immunofluorescence and Western blot analysis demonstrated that QGS suppressed the transfer of Srebp-1 to the nucleus from the cytoplasm, suggesting that the activation of Srebp-1 was inhibited. Our study not only reveals the effects and mechanisms of QGS in the treatment of MAFLD but also sheds new light on the potential value of Chinese herbal medicines for MAFLD treatment.